Tin-carbon negative electrode material and preparation method and application thereof

By depositing and coating tin in the pores of porous carbon to form a tin carbon negative electrode material, the problem of volume expansion of the tin material during the lithium ion deintercalation process is solved, and the circulation stability and specific capacity of the material are improved.

CN119495720APending Publication Date: 2025-02-21LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311027062.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

During the lithium ion deintercalation process, existing tin materials will cause volume expansion and contraction, resulting in material crushing and falling off, affecting cycle stability and specific capacity.

Method used

The tin obtained by decomposing distannane is deposited in pores of porous carbon by vapor deposition, forming a tin-carbon composite material, and subjected to carbon coating to form a tin-carbon negative electrode material with a core-shell structure.

Benefits of technology

It effectively improves the volume expansion phenomenon of tin active substances during charging and discharging, and improves the circulation stability of the material and the first week of the Coulomb efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495720A_ABST
    Figure CN119495720A_ABST
Patent Text Reader

Abstract

The invention discloses a tin-carbon negative electrode material as well as a preparation method and application thereof. The tin-carbon negative electrode material comprises an inner core and a shell, the inner core is a tin-carbon composite material; the shell is a carbon coating layer coating the outer surface of the porous carbon; wherein the tin-carbon composite material comprises porous carbon and tin deposited in pores of the porous carbon; the mass of the porous carbon accounts for 15-95% of the total mass of the tin-carbon composite material; the mass of the tin-carbon composite material accounts for 85-99% of the total mass of the tin-carbon negative electrode material; the mass of tin accounts for 0.1%-85% of the total mass of the tin-carbon negative electrode material, preferably 3%-30%; the tin-carbon composite material is obtained by depositing tin obtained by decomposing distannane in pores of porous carbon through a vapor deposition method; the tin-carbon negative electrode material provided by the invention is used as a negative electrode active material to prepare a negative electrode plate and assemble the negative electrode plate into a secondary battery, so that the first-circle coulombic efficiency of the secondary battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary battery materials, and in particular to a tin-carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] Large-scale energy storage requires that the energy storage system be cheap, safe, green and environmentally friendly. Among the existing large-scale energy storage methods, the electrochemical energy storage system has attracted widespread attention due to its high efficiency and flexibility, and is also a hot research topic at home and abroad. Sodium and silicon elements are very abundant in the earth, widely distributed and simple to refine. Sodium and lithium-ion batteries are the most promising representatives of energy storage technology today. They also have the advantage of low cost and are expected to be used for large-scale energy storage.

[0003] At present, the negative electrode materials of lithium-ion batteries and sodium-ion batteries are mostly carbon materials, such as graphite. However, the theoretical specific capacity of graphite (372 mAh / g) is low, and in practical applications, it is difficult to reach its theoretical specific capacity due to severe charge loss during the formation of the SE I film. Therefore, it cannot meet people's requirements for high energy density electrode materials.

[0004] Tin materials have attracted extensive attention due to their high theoretical specific capacity and working voltage, as well as their high stability and good safety. However, studies have found that the reversible lithium storage capacity of tin (Sn) as a semiconductor material is much greater than that of graphite, but tin will inevitably undergo a volume effect during the lithium ion insertion and extraction process. The tin material electrode will undergo severe volume expansion and contraction during the lithium ion insertion and extraction process, which will cause the material to shatter and fall off, further causing its specific capacity to drop rapidly, affecting its cycle stability, resulting in poor cycle stability, and thus affecting its commercial application.

[0005] How to reduce the volume effect of tin materials and improve the first-cycle efficiency and cycle performance has become a hot issue in current secondary battery research. Therefore, it is necessary to develop a negative electrode material that can have high specific capacity while maintaining high stability and is suitable for commercial applications. Summary of the invention

[0006] The embodiment of the present invention provides a tin-carbon negative electrode material and a preparation method and application thereof. The tin obtained from the decomposed distannane is deposited in the pores of porous carbon by a vapor deposition method to obtain a tin-carbon composite material, and then the tin-carbon composite material is carbon-coated to finally obtain a tin-carbon negative electrode material, wherein the porous carbon matrix has high strength and high hardness, and can effectively improve the volume expansion phenomenon of the tin active substance during the charging and discharging process; at the same time, the carbon coating layer can make the tin-carbon negative electrode material have high cycle stability; the tin particles obtained by directly decomposing and depositing distannane at room temperature have better density and higher purity, and greatly improve the first-cycle coulomb efficiency of the material; the tin-carbon negative electrode material provided by the embodiment of the present invention is applied to a secondary battery, which can effectively improve the first-cycle coulomb efficiency and the first reversible capacity of the secondary battery.

[0007] In a first aspect, an embodiment of the present invention provides a tin-carbon negative electrode material, the tin-carbon negative electrode material comprising a core and an outer shell; the core is a tin-carbon composite material; the outer shell is a carbon coating layer coated on the outer surface of the porous carbon;

[0008] The tin-carbon composite material comprises porous carbon and tin deposited in the pores of the porous carbon; the mass of the porous carbon accounts for 15%-95% of the total mass of the tin-carbon composite material;

[0009] The mass of the tin-carbon composite material accounts for 85%-99% of the total mass of the tin-carbon negative electrode material;

[0010] The mass of the tin accounts for 0.1%-85% of the total mass of the tin-carbon negative electrode material;

[0011] The tin-carbon composite material is obtained by decomposing distannane and depositing tin in the pores of porous carbon by a vapor deposition method.

[0012] Preferably, the particle size D of the porous carbon is 50 The diameter of the porous carbon pores is between 50nm and 50μm; the pore size of the porous carbon pores is between 1nm and 300nm; the porosity of the porous carbon is between 20% and 90%.

[0013] Preferably, the mass of the tin accounts for 3%-30% of the total mass of the tin-carbon negative electrode material;

[0014] The mass of the carbon coating layer accounts for 1%-15% of the total mass of the tin-carbon negative electrode material.

[0015] In a second aspect, an embodiment of the present invention provides a method for preparing the tin-carbon negative electrode material according to the first aspect, the preparation method comprising:

[0016] The porous carbon is placed in a deposition chamber of a vapor deposition furnace, and an inert gas is introduced into the vapor deposition furnace to exhaust air;

[0017] The inert gas is turned off, and a mixed gas of distannane and the inert gas is introduced into the deposition chamber, so that the tin obtained by decomposing the distannane at room temperature is deposited in the pores of the porous carbon to obtain a tin-carbon composite material;

[0018] The tin-carbon composite material is subjected to carbon coating treatment in a coating furnace to form a carbon coating layer, thereby obtaining a tin-carbon negative electrode material with a core-shell structure.

[0019] Preferably, the inert gas includes nitrogen and / or argon; the time for introducing the mixed gas is 30 minutes to 12 hours;

[0020] The mass ratio of the distannane to the inert gas in the mixed gas is [1:1]-[1:10].

[0021] Preferably, the carbon coating treatment method includes: one of gas phase coating, liquid phase coating or solid phase coating;

[0022] The mass of the carbon coating layer accounts for 1%-15% of the total mass of the tin-carbon negative electrode material.

[0023] Further preferably, the solid-phase coated or liquid-phase coated carbon material comprises: one or more of glucose, sucrose, liquid asphalt, phenolic resin, polyvinylidene fluoride, citric acid, polyacrylonitrile, and polyvinyl alcohol;

[0024] The gas-phase coated carbon material includes one or more of methane, ethylene, propylene, acetylene, and natural gas.

[0025] In a third aspect, an embodiment of the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the tin-carbon negative electrode material described in the first aspect.

[0026] In a fourth aspect, an embodiment of the present invention provides a secondary battery, wherein the secondary battery comprises the negative electrode plate described in the second aspect.

[0027] Preferably, the secondary battery includes a lithium ion battery and a sodium ion battery.

[0028] The embodiment of the present invention provides a tin-carbon negative electrode material and a preparation method and application thereof. The tin obtained from the decomposed distannane is deposited in the pores of porous carbon by a vapor deposition method to obtain a tin-carbon composite material. The tin-carbon composite material is then carbon-coated to finally obtain a tin-carbon negative electrode material, wherein the porous carbon matrix is ​​easy to form nano-tin particles in the pores, and has high strength and high hardness, which can effectively improve the volume expansion phenomenon of the tin active substance during the charging and discharging process; at the same time, the carbon coating layer can make the tin-carbon negative electrode material have high cycle stability; the tin particles obtained by directly decomposing and depositing distannane at room temperature have better density and higher purity, and greatly improve the first-cycle coulomb efficiency of the material.

[0029] The tin-carbon negative electrode material provided by the embodiment of the present invention is applied to a secondary battery, which can effectively improve the first cycle coulombic efficiency and the first reversible capacity of the secondary battery.

[0030] The present invention provides a method for preparing a tin-carbon negative electrode material. Since distanane is used as a tin source material for preparing a negative electrode material for a secondary battery, and since distanane itself is a tin-containing gas and can be decomposed at room temperature, there is no need to gasify and decompose at a high temperature, which can reduce energy consumption and greatly reduce manufacturing costs. In addition, the preparation method of the present invention has a simple process, abundant raw materials, no extreme production conditions, and is easy to mass produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.

[0032] Figure 1 is a flow chart of a method for preparing a tin-carbon negative electrode material provided by an embodiment of the present invention;

[0033] Figure 2 It is a schematic diagram of the cross-sectional structure of the tin-carbon negative electrode material provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0035] An embodiment of the present invention provides a tin-carbon negative electrode material, which includes a core and an outer shell; the core is a tin-carbon composite material; the outer shell is a carbon coating layer coated on the outer surface of porous carbon; the mass of the tin-carbon composite material accounts for 85%-99% of the total mass of the tin-carbon negative electrode material.

[0036] The tin-carbon composite material comprises porous carbon and tin deposited in the pores of the porous carbon; the mass of the porous carbon accounts for 15%-95% of the total mass of the tin-carbon composite material; the mass of the tin accounts for 0.1%-85% of the total mass of the tin-carbon negative electrode material, preferably 3%-30%; the tin-carbon composite material is obtained by depositing tin obtained by decomposing ditin alkane in the pores of the porous carbon by vapor deposition, wherein the tin in the pores is attached to the surface of the pore wall in the form of nano-tin particles, and the average particle size range of the nano-tin particles is between 1nm and 300nm.

[0037] The particle size D of the porous carbon used in the present invention is 50 The pore size of porous carbon is between 50nm-50μm; the pore size of porous carbon is between 1nm-300nm, and the porosity is between 20%-90%.

[0038] The present invention provides a method for preparing the above-mentioned tin-carbon negative electrode material. Figure 1 As shown, the specific steps include:

[0039] Step 110, placing porous carbon in a deposition chamber of a vapor deposition furnace, introducing an inert gas into the vapor deposition furnace to exhaust air;

[0040] The inert gas includes nitrogen and / or argon.

[0041] Step 120, turning off the inert gas, introducing a mixed gas of distannane and the inert gas into the deposition chamber, and causing tin obtained by decomposition of distannane at room temperature to be deposited in the pores of the porous carbon, thereby obtaining a tin-carbon composite material;

[0042] The inert gas includes nitrogen and / or argon; the time for introducing the mixed gas is 30 minutes to 12 hours; and the volume ratio of distannane to the inert gas in the mixed gas is [1:1]-[1:10].

[0043] Step 130, subjecting the tin-carbon composite material to a carbon coating treatment in a coating furnace to form a carbon coating layer, thereby obtaining a tin-carbon negative electrode material having a core-shell structure;

[0044] Among them, the carbon coating treatment method includes: one of gas phase coating, liquid phase coating or solid phase coating; the solid phase coated or liquid phase coated carbon material includes: one or more of glucose, sucrose, liquid asphalt, phenolic resin, polyvinylidene fluoride, citric acid, polyacrylonitrile, polyvinyl alcohol; the gas phase coated carbon material includes: one or more of methane, ethylene, propylene, acetylene, natural gas; the mass of the formed carbon coating layer accounts for 1%-15% of the total mass of the tin-carbon negative electrode material.

[0045] The schematic diagram of the cross-sectional structure of the prepared tin-carbon negative electrode material is as follows: Figure 2 As shown, through Figure 2It can be seen that the tin-carbon negative electrode material uses porous carbon as the skeleton, the tin particles are evenly distributed in the pores of the porous carbon, and the surface of the porous carbon is covered with a carbon coating layer.

[0046] The present invention adopts distannane as a tin source material for preparing a negative electrode material of a secondary battery. Since distannane itself is a tin-containing gas and can be decomposed at room temperature, it does not need to be gasified and decomposed at a high temperature, which can reduce energy consumption and greatly reduce manufacturing costs. Moreover, since distannane is in a gaseous state, it is easier to deposit in the pores of porous carbon, and the obtained tin particles have better density and higher purity, thereby greatly improving the first-cycle coulomb efficiency of the material.

[0047] The tin-carbon negative electrode material prepared in the embodiment of the present invention can be used as a negative electrode material active substance for the preparation of a negative electrode sheet. The negative electrode sheet of the present application also includes a negative electrode current collector. The present application has no special restrictions on the negative electrode current collector, as long as it can achieve the purpose of the present application, for example, it can include but is not limited to copper foil, copper alloy foil, nickel foil, stainless steel foil or composite current collector, etc.

[0048] The negative electrode plate of the present application can be used to assemble into a secondary battery, which includes a lithium ion battery or a sodium ion battery.

[0049] The secondary battery prepared by using the tin-carbon negative electrode material provided by the embodiment of the present invention has a lower volume expansion rate, higher first-cycle coulombic efficiency, first reversible capacity and cycle stability.

[0050] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the tin-carbon negative electrode material of the present invention are respectively described below with multiple specific examples.

[0051] Example 1

[0052] This embodiment provides a preparation process and performance test of a tin-carbon negative electrode material. The specific preparation process is as follows.

[0053] (1) At room temperature, 2.5 kg of porous carbon is placed in a deposition chamber of a vapor deposition furnace, and nitrogen is introduced into the vapor deposition furnace to exhaust the air; wherein the porosity of the porous carbon is 20%, and the pore size of the porous carbon is in the range of 3 nm-10 nm.

[0054] (2) Turn off the inert gas and introduce a mixed gas of distannane and nitrogen in a mass ratio of 1:1 into the deposition chamber for 1 hour. The tin obtained by decomposition of distannane at room temperature is deposited in the pores of the porous carbon to obtain a tin-carbon composite material, wherein the mass of tin accounts for 8% of the total mass of the tin-carbon negative electrode material.

[0055] (3) The above-mentioned tin-carbon composite material is subjected to carbon coating treatment in a coating furnace to form a carbon coating layer on the surface of the tin-carbon composite material. The specific method is as follows: 2.5 kg of the tin-carbon composite material is placed in a rotary kiln, the temperature is raised to 650°C under a nitrogen atmosphere, argon gas and acetylene gas are introduced at a volume ratio of 1:1.5 for gas phase coating, the organic gas source is turned off after keeping the temperature for 3 hours, and the material is discharged and graded after cooling to room temperature to obtain a tin-carbon negative electrode material with a core-shell structure.

[0056] The tin-carbon negative electrode material prepared in this embodiment was used to prepare a negative electrode sheet and assemble a 2032-type button half-cell for testing. The specific process is as follows.

[0057] The preparation method of the button half-cell is as follows: the tin-carbon negative electrode material, the conductive additive carbon black, and the adhesive (sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1) are weighed according to a mass ratio of 92%:3%:5%, and the slurry is prepared with a beater, and then coated, dried, and cut into pieces, and assembled into a button half-cell in a glove box.

[0058] The prepared button half-cell was tested in constant current charge and discharge mode using a charge and discharge instrument. The test conditions were: the charge and discharge cut-off voltages were 2V and 0.005V, respectively. After that, the cell was activated at a rate of 0.05C and then the charge and discharge cycle test was performed at a rate of 0.5C. The coulomb efficiency of the first cycle of the test is shown in Table 1.

[0059] Example 2

[0060] This embodiment provides a preparation process and performance test of a tin-carbon negative electrode material. The specific preparation process is as follows.

[0061] (1) At room temperature, 2.5 kg of porous carbon is placed in a deposition chamber of a vapor deposition furnace, and argon gas is introduced into the vapor deposition furnace to exhaust the air; wherein the porosity of the porous carbon is 30%, and the pore size range of the porous carbon is between 20 nm and 40 nm.

[0062] (2) Turn off the inert gas and introduce a mixed gas of distannane and argon in a mass ratio of 1:2 into the deposition chamber for 2 hours. The tin obtained by decomposition of distannane at room temperature is deposited in the pores of the porous carbon to obtain a tin-carbon composite material, wherein the mass of tin accounts for 10% of the total mass of the tin-carbon negative electrode material.

[0063] (3) The above-mentioned tin-carbon composite material is subjected to carbon coating treatment in a coating furnace to form a carbon coating layer on the surface of the tin-carbon composite material. The specific method is as follows: 2.5 kg of the tin-carbon composite material is placed in a rotary kiln, the temperature is raised to 650°C under an argon atmosphere, argon gas and acetylene gas are introduced at a volume ratio of 1:1.5 for gas phase coating, the organic gas source is turned off after keeping the temperature for 3 hours, and the material is discharged and graded after cooling to room temperature to obtain a tin-carbon negative electrode material with a core-shell structure.

[0064] The tin-carbon negative electrode material containing a carbon coating layer prepared in this example was used to prepare a negative electrode sheet and assemble a button-type half-cell, and the assembly and testing methods were the same as in Example 1. The coulombic efficiency of the first test cycle is shown in Table 1.

[0065] Example 3

[0066] This embodiment provides a preparation process and performance test of a tin-carbon negative electrode material. The specific preparation process is as follows.

[0067] (1) At room temperature, 2.5 kg of porous carbon is placed in a deposition chamber of a vapor deposition furnace, and nitrogen is introduced into the vapor deposition furnace to exhaust the air; wherein the porosity of the porous carbon is 40%, and the pore size of the porous carbon is in the range of 20 nm to 60 nm.

[0068] (2) Turn off the inert gas and introduce a mixed gas of distannane and nitrogen in a mass ratio of 1:4 into the deposition chamber for 3 hours. The tin obtained by decomposition of distannane at room temperature is deposited in the pores of the porous carbon to obtain a tin-carbon composite material, wherein the mass of tin accounts for 20% of the total mass of the tin-carbon negative electrode material.

[0069] (3) The above-mentioned tin-carbon composite material is subjected to carbon coating treatment in a coating furnace to form a carbon coating layer on the surface of the tin-carbon composite material. The specific method is as follows: 2.5 kg of the tin-carbon composite material is placed in a rotary kiln, the temperature is raised to 650°C under an argon atmosphere, argon gas and ethylene gas are introduced at a volume ratio of 1:1.5 for gas phase coating, the organic gas source is turned off after keeping the temperature for 4 hours, and the material is discharged and graded after cooling to room temperature to obtain a tin-carbon negative electrode material with a core-shell structure.

[0070] The tin-carbon negative electrode material containing a carbon coating layer prepared in this example was used to prepare a negative electrode sheet and assemble a button-type half-cell, and the assembly and testing methods were the same as in Example 1. The coulombic efficiency of the first test cycle is shown in Table 1.

[0071] Example 4

[0072] This embodiment provides a preparation process and performance test of a tin-carbon negative electrode material. The specific preparation process is as follows.

[0073] (1) At room temperature, 2.5 kg of porous carbon is placed in a deposition chamber of a vapor deposition furnace, and nitrogen is introduced into the vapor deposition furnace to exhaust the air; wherein the porosity of the porous carbon is 50%, and the pore size of the porous carbon is in the range of 50 nm-90 nm.

[0074] (2) Turn off the inert gas and introduce a mixed gas of distannane and nitrogen in a mass ratio of 1:6 into the deposition chamber for 4 hours. The tin obtained by decomposition of distannane at room temperature is deposited in the pores of the porous carbon to obtain a tin-carbon composite material, wherein the mass of tin accounts for 18% of the total mass of the tin-carbon negative electrode material.

[0075] (3) The above-mentioned tin-carbon composite material is subjected to carbon coating treatment in a coating furnace to form a carbon coating layer on the surface of the tin-carbon composite material. The specific method is as follows: 2.5 kg of the tin-carbon composite material is placed in a rotary kiln, the temperature is raised to 700°C under an argon atmosphere, argon gas and ethylene gas are introduced at a volume ratio of 1:1.5 for gas phase coating, the organic gas source is turned off after keeping the temperature for 3 hours, and the material is discharged and graded after cooling to room temperature to obtain a tin-carbon negative electrode material with a core-shell structure.

[0076] The tin-carbon negative electrode material containing a carbon coating layer prepared in this example was used to prepare a negative electrode sheet and assemble a button-type half-cell, and the assembly and testing methods were the same as in Example 1. The coulombic efficiency of the first test cycle is shown in Table 1.

[0077] Example 5

[0078] This embodiment provides a preparation process and performance test of a tin-carbon negative electrode material. The specific preparation process is as follows.

[0079] (1) At room temperature, 3.5 kg of porous carbon is placed in a deposition chamber of a vapor deposition furnace, and nitrogen is introduced into the vapor deposition furnace to exhaust the air; wherein the porosity of the porous carbon is 60%, and the pore size of the porous carbon is in the range of 50 nm-100 nm.

[0080] (2) Turn off the inert gas and introduce a mixed gas of distannane and nitrogen in a mass ratio of 1:8 into the deposition chamber for 8 hours. The tin obtained by decomposition of distannane at room temperature is deposited in the pores of the porous carbon to obtain a tin-carbon composite material, wherein the mass of tin accounts for 25% of the total mass of the tin-carbon negative electrode material.

[0081] (3) The above-mentioned tin-carbon composite material is subjected to carbon coating treatment in a coating furnace to form a carbon coating layer on the surface of the tin-carbon composite material. The specific method is as follows: 3.5 kg of the tin-carbon composite material is placed in a rotary kiln, the temperature is raised to 850°C under an argon atmosphere, argon and natural gas are introduced in a volume ratio of 1:1 for gas phase coating, the organic gas source is turned off after keeping the temperature for 4 hours, and the material is discharged and graded after cooling to room temperature to obtain a tin-carbon negative electrode material with a core-shell structure.

[0082] The tin-carbon negative electrode material containing a carbon coating layer prepared in this example was used to prepare a negative electrode sheet and assemble a button-type half-cell, and the assembly and testing methods were the same as in Example 1. The coulombic efficiency of the first test cycle is shown in Table 1.

[0083] Example 6

[0084] This embodiment provides a preparation process and performance test of a tin-carbon negative electrode material. The specific preparation process is as follows.

[0085] (1) At room temperature, 2.5 kg of porous carbon is placed in a deposition chamber of a vapor deposition furnace, and argon gas is introduced into the vapor deposition furnace to exhaust the air; wherein the porosity of the porous carbon is 60%, and the pore size of the porous carbon is in the range of 50 nm-200 nm.

[0086] (2) Turn off the inert gas and introduce a mixed gas of distannane and argon in a mass ratio of 1:10 into the deposition chamber for 10 hours. The tin obtained by decomposition of distannane at room temperature is deposited in the pores of the porous carbon to obtain a tin-carbon composite material, wherein the mass of tin accounts for 3% of the total mass of the tin-carbon negative electrode material.

[0087] (3) The above-mentioned tin-carbon composite material is subjected to carbon coating treatment in a coating furnace to form a carbon coating layer on the surface of the tin-carbon composite material. The specific method is as follows: 2.5 kg of the tin-carbon composite material is placed in a rotary kiln, the temperature is raised to 650°C under a nitrogen atmosphere, argon gas and natural gas are introduced at a volume ratio of 1:1.5 for gas phase coating, the organic gas source is turned off after keeping the temperature for 3 hours, and the material is discharged and graded after cooling to room temperature to obtain a tin-carbon negative electrode material with a core-shell structure.

[0088] The tin-carbon negative electrode material containing a carbon coating layer prepared in this example was used to prepare a negative electrode sheet and assemble a button-type half-cell, and the assembly and testing methods were the same as in Example 1. The coulombic efficiency of the first test cycle is shown in Table 1.

[0089] In order to better illustrate the effect of the embodiment of the present invention, a comparative example is compared with the above embodiment.

[0090] Comparative Example 1

[0091] This embodiment provides a preparation process and performance test of a negative electrode material. The negative electrode material is different from that of Example 1 in that porous SiC is used as a matrix instead of porous carbon. The raw materials and process parameters used in other preparation processes are the same as those of Example 1.

[0092] The negative electrode material prepared in this comparative example was used to prepare a negative electrode sheet and assemble a button-type half-cell, and the assembly and testing methods were the same as those in Example 1. The coulombic efficiency of the first test cycle is shown in Table 1.

[0093] Comparative Example 2

[0094] This embodiment provides a process for preparing a negative electrode material. The negative electrode material is different from that in Embodiment 1 in that it does not have a carbon coating layer. The raw materials and process parameters used in other preparation processes are the same as those in Embodiment 1.

[0095] The negative electrode material prepared in this comparative example was used to prepare a negative electrode sheet and assemble a button-type half-cell, and the assembly and testing methods were the same as those in Example 1. The coulombic efficiency of the first test cycle is shown in Table 1.

[0096] Comparative Example 3

[0097] This embodiment provides a process for preparing a negative electrode material. The difference between this negative electrode material and that of Embodiment 1 is that di-stannane is not used as a tin source material, but a gas formed by SnCl4 at a temperature greater than the boiling point is used. The raw materials and process parameters used in other preparation processes are the same as those of Embodiment 1.

[0098] The negative electrode material prepared in this comparative example was used to prepare a negative electrode sheet and assemble a button-type half-cell, and the assembly and testing methods were the same as those in Example 1. The coulombic efficiency of the first test cycle is shown in Table 1.

[0099] Table 1 is a summary of the first cycle coulombic efficiency of button-type half-cells assembled in Examples 1-6 and Comparative Examples 1-3:

[0100]

[0101]

[0102] By comparing the data in Table 1, it can be seen that the first-cycle coulombic efficiency of the button half-cells of Examples 1-6 is greater than that of Comparative Examples 1-3. This is because the tin-carbon negative electrode material prepared in the embodiments of the present invention is a tin-carbon composite material obtained by depositing the tin obtained from the decomposed distannane in the pores of porous carbon by a vapor deposition method, and then the tin-carbon composite material is subjected to carbon coating treatment to finally obtain a tin-carbon negative electrode material, wherein the porous carbon matrix has high strength and high hardness, and can effectively improve the volume expansion phenomenon of the tin active substance during the charge and discharge process; at the same time, the carbon coating layer can make the tin-carbon negative electrode material have high cycle stability; the tin particles obtained by directly decomposing and depositing distannane at room temperature have better density and higher purity, and greatly improve the first-cycle coulombic efficiency of the material. Under the synergistic effect of these three aspects, the tin-carbon negative electrode materials prepared in Examples 1-6 of the present invention have a higher first-cycle coulombic efficiency when used in a battery, that is, the tin-carbon negative electrode materials prepared in Examples 1-6 of the present invention have a higher reversible specific capacity.

[0103] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A tin-carbon negative electrode material, characterized in that: The tin-carbon negative electrode material comprises a core and an outer shell; the core is a tin-carbon composite material; the outer shell is a carbon coating layer coated on the outer surface of the porous carbon; The tin-carbon composite material comprises porous carbon and tin deposited in the pores of the porous carbon; the mass of the porous carbon accounts for 15%-95% of the total mass of the tin-carbon composite material; The mass of the tin-carbon composite material accounts for 85%-99% of the total mass of the tin-carbon negative electrode material; The mass of the tin accounts for 0.1%-85% of the total mass of the tin-carbon negative electrode material; The tin-carbon composite material is obtained by decomposing distannane and depositing tin in the pores of porous carbon by a vapor deposition method.

2. The tin-carbon negative electrode material according to claim 1, characterized in that The particle size D of the porous carbon 50 The diameter of the porous carbon pores is between 50nm and 50μm; the pore size of the porous carbon pores is between 1nm and 300nm; the porosity of the porous carbon is between 20% and 90%.

3. The tin-carbon negative electrode material according to claim 1, characterized in that The mass of the tin accounts for 3% to 30% of the total mass of the tin-carbon negative electrode material; The mass of the carbon coating layer accounts for 1%-15% of the total mass of the tin-carbon negative electrode material.

4. A method for preparing the tin-carbon negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: The porous carbon is placed in a deposition chamber of a vapor deposition furnace, and an inert gas is introduced into the vapor deposition furnace to exhaust air; The inert gas is turned off, and a mixed gas of distannane and the inert gas is introduced into the deposition chamber, so that the tin obtained by decomposing the distannane at room temperature is deposited in the pores of the porous carbon to obtain a tin-carbon composite material; The tin-carbon composite material is subjected to carbon coating treatment in a coating furnace to form a carbon coating layer, thereby obtaining a tin-carbon negative electrode material with a core-shell structure.

5. The preparation method according to claim 4, characterized in that: The inert gas includes nitrogen and / or argon; the time for introducing the mixed gas is 30 minutes to 12 hours; The mass ratio of the distannane to the inert gas in the mixed gas is [1:1]-[1:10].

6. The preparation method according to claim 4, characterized in that: The carbon coating treatment method includes: one of gas phase coating, liquid phase coating or solid phase coating; The mass of the carbon coating layer accounts for 1%-15% of the total mass of the tin-carbon negative electrode material.

7. The preparation method according to claim 6, characterized in that: The solid-phase coated or liquid-phase coated carbon material includes one or more of glucose, sucrose, liquid asphalt, phenolic resin, polyvinylidene fluoride, citric acid, polyacrylonitrile, and polyvinyl alcohol; The gas-phase coated carbon material includes one or more of methane, ethylene, propylene, acetylene, and natural gas.

8. A negative electrode plate, characterized in that: The negative electrode plate comprises the tin-carbon negative electrode material described in any one of claims 1-2 above.

9. A secondary battery, characterized in that: The secondary battery comprises the negative electrode sheet as claimed in claim 8.

10. The secondary battery according to claim 9, characterized in that: The secondary batteries include lithium ion batteries and sodium ion batteries.

Citation Information

Cited By

  • Lithium ion battery electrode material and preparation method thereof

    CN121260767A

  • Tin-carbon composite material, and preparation method therefor and use thereof

    WO2026183950A1